2009
DOI: 10.1038/embor.2009.102
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming during wound healing: loss of polycomb‐mediated silencing may enable upregulation of repair genes

Abstract: Tissue repair is a complex process that requires wound-edge cells to proliferate and migrate, which in turn necessitates induction of a large repair transcriptome. Epigenetic modifications have emerged as crucial regulators of gene expression. Here, we ask whether epigenetic reprogramming might contribute to the concerted induction of repair genes by wound-edge cells. Polycomb group proteins (PcGs) co-operatively silence genes by laying down repressive marks such as histone H3 lysine 27 trimethylation (H3K27me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
148
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(163 citation statements)
references
References 28 publications
15
148
0
Order By: Relevance
“…Moreover, only full-thickness wounds induce the migration of cells from neighboring HFs to the place of injury. The molecular mechanism underlying both the attraction and homing of potential tumor-initiating cells or cells contributing to tumor formation remains an important topic for future studies and is likely to depend on the specific cytokine and growth factor milieu and involve alteration of epigenetic patterns (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only full-thickness wounds induce the migration of cells from neighboring HFs to the place of injury. The molecular mechanism underlying both the attraction and homing of potential tumor-initiating cells or cells contributing to tumor formation remains an important topic for future studies and is likely to depend on the specific cytokine and growth factor milieu and involve alteration of epigenetic patterns (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recent genome-wide mapping of sites on chromatin that contain H3K27me3 and are bound by PcG proteins have identified hundreds of putative Polycomb target genes in Drosophila and several thousand in human cells (7)(8)(9)(10). In addition to their well-established role in maintaining cell identities, PcG proteins have been implicated in many processes relevant to aging, including stem cell pluripotency and self-renewal, regulation of cell cycle exit, regeneration and wound healing, tumorigenesis, and DNA repair, suggesting that PcG proteins may also modulate organismal life span (1,(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Shaw and Martin postulated that PcG proteins may play important roles in wound repair, and found that the expression of PRC2 complex components Ezh2, Suz12, and Eed was transiently downregulated during wound healing in in vivo murine models. 61 Additionally, immunohistochemical expression patterns illustrated a paucity of Eed and Ezh2 at the wound margin, while it was abundant further away from the wound. 61 In contrast, the expression of H3K27 histone demethylases JMJD3 and Utx was upregulated.…”
Section: Dynamic Expression Patterns Of Epigenetic Regulators During mentioning
confidence: 99%
“…61 Additionally, immunohistochemical expression patterns illustrated a paucity of Eed and Ezh2 at the wound margin, while it was abundant further away from the wound. 61 In contrast, the expression of H3K27 histone demethylases JMJD3 and Utx was upregulated. Levels of both Eed and Ezh2 were, however, restored once re-epithelialization was complete, suggesting that there is a transient activation of repair genes via loss of PcG-proteinmediated silencing to permit epithelial closure.…”
Section: Dynamic Expression Patterns Of Epigenetic Regulators During mentioning
confidence: 99%
See 1 more Smart Citation